Case Study Of Dft (Deep Flow Technique)- Nft (Nutrient Flow Technique) Hydroponic Planting Patterns In First Middle School Students State 1 And 5 Karangploso Malang - Dina Wahyu Indriani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
The Deep Flow Technique (DFT) method combined with the Nutrient Film Technique system. The purpose of this service activity is the first to organize training on the manufacture of simple DFT-NFT hydroponics, with methods and materials that are safe to use and serve as material for debriefing and providing entrepreneurial motivation for community groups in Malang district. The implementation of this service is at SMP N 1 and SMPN 5 Karangploso, Malang Regency. The webinar participants were attended by 61 participants consisting of 8th and 9th grade students, accompanying teachers, and a team of service lecturers. As for the results of this activity 81% of the webinar participants are familiar with the pattern of farming using the DFT NFT hydroponic system well. So that participants have benefited from this activity and these academics are able to apply knowledge to society significantly.